MATHEMATICS CONNECTIONS VIEWED FROM ADVERSITY QUOTIENT IN LMS ASSISTED PROBLEM BASED LEARNING IN SMA - Lilik Supono; Arief Agoestanto (Universitas Sembilanbelas November Kolaka, 2023)
The connection between mathematics and adversity quotient (AQ) has an important role in a person's ability to make decisions to solve problems in life. The Problem-based learning (PBL) model assisted by the Learning Management System (LMS) is a learning that utilizes technology combining PBL models and LMS assisted learning. This study aims to (1) examine the effectiveness of LMS-assisted PBL to improve high school students' mathematical connection skills, (2) examine the effect of AQ on students' mathematical connection abilities in LMS-assisted PBL learning. This research is a mixed method research with a sequential explanatory design with a larger quantitative portion than the qualitative one. The population of this study was class XI students of SMA N 1 Ungaran, Semarang Regency. Quantitative data were selected by simple random sampling technique. Qualitative data was taken based on the students' AQ. Quantitative data analysis techniques with parametric statistics such as average test, classical completeness test, and regression test. Qualitative data analysis techniques using data reduction, presentation, and drawing conclusions. The results showed that (1) LMS-assisted PBL learning was effective in increasing students' mathematical connections (2) there was an influence of AQ on students' mathematical connection abilities in LMS-assisted PBL learning.